Localized translation near the mitochondrial outer membrane: An update - Lesnik, Chen (RNA Biol, 2015)
Local synthesis of proteins near their activity site has been demonstrated in many biological systems, and has diverse contributions to cellular functions. Studies in recent years have revealed that hundreds of mitochondria-destined proteins are synthesized by cytosolic ribosomes near the mitochondrial outer membrane, indicating that localized translation also occurs at this cellular locus. Furthermore, in the last year central factors that are involved in this process were identified in yeast, Drosophila, and human cells. Herein we review the experimental evidence for localized translation on the cytosolic side of the mitochondrial outer membrane; in addition, we describe the factors that are involved in this process and discuss the conservation of this mechanism among various species. We also describe the relationship between localized translation and import into the mitochondria and suggest avenues of study that look beyond cotranslational import. Finally we discuss future challenges in characterizing the mechanisms for localized translation and its physiological significance.